2018
DOI: 10.1177/1940161218819430
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Opportunity Structures for Populist Communication: Comparing Different Types of Politicians and Issues in Social Media, Television and the Press

Abstract: The aim of this study is to explore favorable opportunity structures for populist communication of politicians in Western democracies. We analyze the content and style of 2,517 statements from 103 politicians from six countries (France, Italy, Germany, Switzerland, United Kingdom, and United States) who differ in their party affiliation (populist versus nonpopulist) and hierarchical position (backbencher vs. frontbencher). To learn more about their media strategies and chances of success, we investigate four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 43 publications
6
78
0
5
Order By: Relevance
“…In country clusters where scapegoats are most accessible in receivers' schemata, populist blame attributions should thus be most effective. These findings support the notion that populist communication is most effective when it resonates with real-life, contextuallevel opportunity structures (e.g., Aalberg et al, 2017;Ernst, Esser, Blassnig, & Engesser, 2018;Reinemann et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…In country clusters where scapegoats are most accessible in receivers' schemata, populist blame attributions should thus be most effective. These findings support the notion that populist communication is most effective when it resonates with real-life, contextuallevel opportunity structures (e.g., Aalberg et al, 2017;Ernst, Esser, Blassnig, & Engesser, 2018;Reinemann et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…As our conceptualization relied on the "ideational approach," which bears good operationalizability (Mudde, 2017: 39), we are confident that the key elements and principles of sciencerelated populism can be usefully translated into survey scales, coding schemes for standardized content analyses, or qualitative approaches to text, corpus, or discourse analysissimilar to those that have been developed for measurements of political populism (e.g. Ernst et al, 2019;Hameleers, 2019;Schulz et al, 2018). This would allow for comprehensive investigations of individuals' science-related populist attitudes (the "demand side" of science-related populism) and science-related populist communication of public figures and organizations (the "supply side").…”
Section: Science-related Populism and Its Implicationsmentioning
confidence: 99%
“…Since a huge amount of speeches and debates are involved in presidential campaigns, language is a key element during the election period. Many researchers have actually identified that language is a powerful weapon for the success of many politicians (Tenorio, 2002;Ricks, 2018;Ernst, Esser, Blassnig, & Engesser, 2019). In view of that, the research aims to compare the two candidates' language styles to dig out the secret of Trump's incredible victory over Clinton.…”
Section: Introductionmentioning
confidence: 99%